Assessing Organic Poultry Farming Knowledge Among Tribal Farmers: A Tailored Knowledge Test (Indian Journal of Extension Education, 2023)
The increasing demand for organic agricultural products necessitates the assessment of farmers’ knowledge levels, particularly among tribal communities engaged in organic poultry farming. This manuscript presents the construction and development of a knowledge test specifically designed for tribal farmers in India who have undergone training in organic poultry farming. The test aims to evaluate their understanding of organic farming principles, best practices, disease management, and other relevant aspects. A total of 56 items were selected, and their difficulty and discrimination indices were calculated using item analysis. The final selection of items for the test was based on criteria of difficulty and discrimination indices. The reliability of the test was assessed using the split-half method, yielding a correlation coefficient of 0.82. The validity of the test was established through point biserial correlation analysis. The developed knowledge test provides a valuable tool for evaluating the productivity of training programmes and identifying areas for further support and improvement in organic poultry farming among tribal farmers.